An Experimental Analysis of Network Planning - King, William R.; Lukas, Paul A. (Management Science, 1973)
This study (1) tests some basic hypotheses related to the use of historical estimating behavioral information in network planning, and (2) makes comparative evaluations of a number of network planning techniques. Since a number of previous studies have evaluated similar hypotheses and techniques to a limited degree using data from real-world projects, this study utilizes a laboratory experiment as a means of generating data which have a richer potential for analysis. Although the results are not conclusive, the study further suggests the potential value of using historical estimating behavior as a basis for “adjusting” the single time estimates made by an individual or group and/or using a single-estimate simulation approach rather than using a multiple estimate approaches such as PERT.